TANTANGAN INDEPENDENSI MEDIA DALAM PEMILU: KASUS KOMPAS.COM - Khotimah, Nurul (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2019)
The aim of this study is to describe media ideology and construct media independence in the 2019 political year. Ideology has a major influence on the determination of media content. It is as if the general election democracy party cannot be separated from the mass media, so that the reporting of events